The role of the transportation agency in improving public transportation services: case study of the binjai city transporta-tion office - Oktavia Nadela; Raja Sakti Putra Harahap (Law and Economics, 2025)
The role of the transportation agency in improving public transportation services. This study is based on the reality that the transportation official of Binjai city has played important role to manage this transportation issue. One effort by the transportation official of Binjai city in relation with public service is to improve urban transport survive given to the public. Based on result of research, it is acknowledged that transportation official of Binjai city plays three roles within public service improvement. The transportation official may act as regulator to make a policy or a regulation concerning with urban transport, can be a facilitator or institution which provides structure and infrastructure related to urban transport, and also works as evaluator to watch over every policy and each available structure and infrastructure. The improvement effort of public service can bring positive and negative responses. Therefore, the cooperation should be needed between the government and the public to improve service quality in urban transport sector.